SYNTHESIS AND BIOLOGICAL EVALUATION OF SOME SULFONAMIDE SCHIFF’S BASES (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Substituted sulfonamides were reacted with different aromatic aldehydes to form Schiff’s bases. TLC ascertained the purity of synthesized compounds on silica gel G coated plates and visualized by using iodine vapour. The structures of synthesized compounds were confirmed by their IR, 1H NMR spectroscopic data. The derivatives were subjected to antimicrobial activity using different bacterial strains (Klebsiella pneumoniae, gram negative bacteria and Staphylococcus epidermidis, Bacillus subtilis as gram positive bacteria with respect to Ciprofloxacin as standard antibiotics.